Effect of Electropulsing on Nanostructured Bainitic Steel - Agrawal M.; Bhuyan D.; Pandey R.K.; Sharma A.; Manna R. (My University, 2025)
Novel steel of Fe-0.81C-1.9Mn-1.48Si-0.27Mo-0.95Ni-1.43Co-0.79Al composition was austenitized at 930 °C and isothermally treated at 240 °C for different intervals of time to produce carbide-free nanostructured bainite. The metastable austenite transformed to nanostructured bainite without any carbide precipitation. The transformation was slow but isothermal in nature, i.e., volume fraction of transformed product was increasing with time. The stability of phases was investigated under electropulsing at a high peak current density of 8.3 kA/mm2 and a low total pulse duration of 265 μs. Electropulsing drove cementite precipitation kinetics in both austenite and bainite even in the presence of high silicon content of 1.48 mass%. Thereby major part of metastable carbon lean austenite transformed to bainite in a few microseconds. As a result, the remaining austenite changed its morphology from a blocky form toward a desirable filmy form. Precipitation in bainite restricted its growth and nanostructure was maintained. The overall hardness of the steel was decreased due to reduction in residual strain, dislocation density although austenite was transformed to bainite, and precipitation of cementite, but hardness was much higher than that of coarse-grained ferrite. Electropulsing of nanostructured bainite increases the elastic modulus by the combined effect of transformation of retained austenite to bainite and cementite precipitation in austenite/bainite. © 2021, ASM International.